Environmental Liability and Organizational Structure - F.P. de Vries
This paper presents a multitask principal-agent model to examine how environmental liability rules for individual managers within a corporate hierarchy affect, on the one hand, the incentive schemes the organization provides and, on the other hand, the choice between a functional or a product-based organizational structure. If managers are risk neutral, a product-based organization dominates a functional organization and allows to obtain first-best effort level. If, moreover, there are no diseconomies of span, both organizational forms are equivalent. It is also shown that for the dominant function, effort levels are higher in a product-based organization than in a functional one. With risk averse managers, no organizational structure dominates the other in general, but we are able to identify under which conditions it does not matter who is held liable for environmental damages.contracts, liability, firm structure, principal-agent